PERAN JAM'IYYAH IJTIMA'IYYAH DALAM PEMBENTUKAN TRADISI - Anshori, Mohammad; Mustaqim, Muhamad (LP2M IAIN kUDUS, 2014)
THE ROLE OF THE JAM’IYYAH IJTIMA’IYYAH IN THE FORMATION OF TRADITIONS. Nahdlotul Ulama is a religious social organization which follow the ahlus sunnah wal jama’ah, by preserving the society tradition. The Mitung Dinatradition is a tradition of Islam that has been acculturated by indigenous traditions. Mitung dinatradition is a multi colored diversity of NU which has been grown. Technically, the tradition of mitung dina sometimes brings its own burden for the families left behind. Then, it becomes a separate discussion for the jam’iyyah board, to make changes to the tradition became more ease. Based on the results of the research, it can be inferred that the jam’iyyah NU subsection Kedung Banteng has committed changes to the ritual mitung dinaor ngajekno in village Kedung Banteng Subdistrict Karangayar Demak regency